PENCEGAHAN PENYAKIT GIGI MELALUI PENYULUHAN, KURATIF SEDERHANA DAN SIKAT GIGI SDN TUNGKARAN KABUPATEN BANJAR - Fansurna, Anderi (UPPM Poltekkes Kemenkes Banjarmasin, 2023)
Initial knowledge about the community's dental and oral health was on average 55.60 (medium) after counseling increased quite significantly to an average knowledge of 66.63 (high) (Syahputri et al., n.d.). When examining the caries experience (DMF-T) of 116 students, it was found that the average DMF-T number was 2.32 (in the medium category). After treatment was carried out, the caries number could be reduced to 0.77 (low category), achieving the DMF-T reduction rate. T can be maximized because all students are cooperative so that cavities can be filled/simple procedures can be done. Business Activities to reduce the number of cavities/caries from 180 cases to 0 cases of which 180 cases can be carried out with simple fillings (100%). Meanwhile, the Performance Treatment Index (PTI) in this activity increased quite significantly, from 0% to 100%, this was because the students were cooperative and understood how to maintain good and correct dental health.